2018
DOI: 10.1111/1759-7714.12758
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of HOXA13 sensitizes human esophageal squamous cell carcinoma to chemotherapy

Abstract: BackgroundChemoresistance often develops in esophageal squamous cell carcinoma (ESCC), leading to poor prognosis. HOX genes play a crucial role in embryonic development and cell differentiation. Studies have recently linked HOX with chemoresistance, thus we explored whether HOXA13 is involved in ESCC chemoresistance.MethodsOne hundred thirty‐one ESCC patients who received neoadjuvant chemotherapy were enrolled. HOXA13 expression was examined by immunohistochemistry. RNA interference was used to knock down the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The coordinated expression of HOXA13, ANXA2 and SOD2 strongly predicts poor prognosis in ESCC [47]. HOXA13 is also involved in the modulation of EMT in ESCC cells [48]. In ESCC patients treated with neoadjuvant chemotherapy, HOXA13 expression is associated with the worst tumor regression grade.…”
Section: Hoxa13mentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinated expression of HOXA13, ANXA2 and SOD2 strongly predicts poor prognosis in ESCC [47]. HOXA13 is also involved in the modulation of EMT in ESCC cells [48]. In ESCC patients treated with neoadjuvant chemotherapy, HOXA13 expression is associated with the worst tumor regression grade.…”
Section: Hoxa13mentioning
confidence: 99%
“…In ESCC patients treated with neoadjuvant chemotherapy, HOXA13 expression is associated with the worst tumor regression grade. The knockdown of HOXA13, in ESCC cells, increases cis-platinum-induced apoptosis, suggesting an essential role of HOXA13 in drug-resistance acquisition [48]. In a further investigation, an opposite trend of HOXA13 expression has been detected in oral squamous cell carcinoma (OSCC): a prevalent HOXA13 expression, in the superficial side of the lesions, is significantly associated to a better prognosis of OSCC patients [27].…”
Section: Hoxa13mentioning
confidence: 99%
“…HOXA13 knockdown significantly restored the epithelial characteristics and reduced the mesenchymal characteristics of the cancer cells via the transforming growth factor (TGF)-β signaling pathway (35). Moreover, HOXA13 expression negatively affects cisplatin sensitivity in human esophageal squamous cells and overall survival in patients with esophageal squamous cell carcinoma (38). Our results showed that multiple cancer-associated pathways were identified in LSCC tissues with high expression of HOXA13, and high expression of HOXA13 in LSCC predicted poor overall survival.…”
Section: Discussionmentioning
confidence: 64%
“…Accumulating evidence have indicated that multiple molecules were involved in anticancer drug resistance of ESCC 9,2631. For example, IL6 was found to promote chemoresistance in ESCC via CXCR7,26 and downregulation of HOXA13 sensitizes human ESCC to chemotherapy and might regulate epithelial-to-mesenchymal transition (EMT) 30. CDC7 has been reported to promote tumor chemoresistance and survival via multiple pathways 20.…”
Section: Discussionmentioning
confidence: 99%